2014
DOI: 10.1080/14786419.2014.900768
|View full text |Cite
|
Sign up to set email alerts
|

In vitroantioxidant and antimicrobial activities of flavonoids fromPanax notoginsengflowers

Abstract: Panax notoginseng and its flowers are both well-known traditional Chinese medicinal herbs. To date, antimicrobial and antioxidant activities of flavonoids from P. notoginseng flowers (PNF) remain unclear. In this study, antimicrobial and antioxidant activities of flavonoids from PNF were investigated. The crude flavonoids were purified using a column (25 cm × 1.5 cm) packed with AB-8 macroporous adsorption resin. Compared with ascorbic acid, the purified flavonoids excelled in scavenging activities on 2,2'-azi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Many chronic degenerative diseases and cancer have a direct or indirect relationship with the damaging effects of free radicals (Bielli, Scioli, Mazzaglia, Doldo, & Orlandi, 2015). Medicines possessing antioxidant activity can reduce oxidative stress injury caused by free radicals (Hong, Hu, Liu, Zhou, & Zhao, 2014;Liu & Jiang, 2012;Zhou, Tang, Keep, Ma, & Xiang, 2014). Many components of S. miltiorrhiza Bge.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Many chronic degenerative diseases and cancer have a direct or indirect relationship with the damaging effects of free radicals (Bielli, Scioli, Mazzaglia, Doldo, & Orlandi, 2015). Medicines possessing antioxidant activity can reduce oxidative stress injury caused by free radicals (Hong, Hu, Liu, Zhou, & Zhao, 2014;Liu & Jiang, 2012;Zhou, Tang, Keep, Ma, & Xiang, 2014). Many components of S. miltiorrhiza Bge.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Plant-derived flavonoids have multifold activities and the best described pharmacological activity of flavonoids is to act as potent natural-based antioxidant (Sarian et al, 2017). Moreover, a growing number of articles have demonstrated that antioxidant flavonoids always possess antimicrobial activities in vitro (Erasto et al, 2004;Liu et al, 2010;Hong et al, 2014;de Camargo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Panax notoginseng (Burk.) F. H. Chen, of the family Araliaceae, is a traditional Chinese medicinal plant (Hong et al 2014). Notoginsenoside R1 and ginsenosides Rg1, Rd, Re, and Rb1 are its principal active constituents, which endow a wide range of pharmacological activities, such as anti-inflammatory, antifatigue, and hepato-protection effects, and coronary heart disease prevention (Li et al 2007;Xia et al 2016).…”
mentioning
confidence: 99%